Association between rehabilitation after reperfusion treatment and in-hospital mortality: Results from a national registry study - Li, Shengde; Fang, Shiyuan; Zhang, Dingding; Lu, Yixiu; Wang, Longde; Peng, Bin (Frontiers in Neurology, 2022)
Background There is no effective regimen to reduce the mortality in patients treated with intravenous thrombolysis or endovascular therapy (EVT). Therefore, we aimed to examine whether sequential therapy of rehabilitation could effectively reduce in-hospital mortality in patients treated with reperfusion therapy. Methods This is a prospective registry study included ischemic stroke patients, who were treated with intravenous thrombolysis or endovascular therapy, at Stroke Center Work Plan in China between October 1, 2018 and July 31, 2020. Patients were divided into 2 groups: those with (IRT+) or without (IRT−) inpatient rehabilitation therapy (IRT). The primary outcome was all-cause in-hospital mortality. We used Cox proportional hazards models and propensity-score matching analysis to calculate hazard ratios (HRs) for mortality in thrombolysis-only and EVT groups, respectively. Results Of the 189519 patients in thrombolysis-only group, 35.7% were female, and the median (interquartile range, IQR) age, onset-to-needle time, and follow-up time were 66 (57-74) years, 165(119-220) minutes, and 9 (5-12) days, respectively. Among the 45211 patients in EVT group, 35.9% were female, and the median (interquartile range, IQR) age, onset-to-puncture time, and follow-up time were 66 (56-74) years, 297 (205-420) minutes, and 11 (6-16) days, respectively. In the thrombolysis-only group with median (IQR) initial National Institutes of Health Stroke Scale (NIHSS) score of 6 (3-11), 105244 patients (55.5%) treated with IRT had significantly lower all-cause in-hospital mortality (0.6% vs 2.3%; adjusted HR, 0.18 [95% confidence interval (CI), 0.16-0.20]). In EVT group with median (IQR) initial NIHSS score of 15 (10-20), 31098 patients (68.8%) treated with IRT also had significantly lower all-cause in-hospital mortality (2.0% vs 12.1%; adjusted HR, 0.13[95% CI, 0.12-0.15]). IRT remained significantly associated with reduced in-hospital mortality in sensitivity, subgroup and propensity-score matching analyses among both thrombolysis-only and EVT groups, respectively. Conclusion Among ischemic patients treated with intravenous thrombolysis or EVT, sequential therapy of rehabilitation was associated with markedly lower all-cause in-hospital mortality. These findings provide direct evidence on promoting inpatient rehabilitation therapy in patients receiving reperfusion therapy.